METHODS OF CALCULATING HARM AND ENVIROMENTAL DAMAGE AND THEIR LEGAL BASIS - Краснова, М. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article deals with the methods of economic assessment of harm from environmental pollution.